A randomized control trial to assess optical coherence tomography parameters of the Xlimus drug-eluting stent: the XLIMIT trial - Testa, Luca; Squillace, Mattia; Ventrella, Nicoletta; Moreno, Raul; Jiménez-Valero, Santiago; Serra, Antoni; Gomez Hospital, Joan Antoni; Bellamoli, Michele; Popolo Rubbio, Antonio; Bedogni, Francesco (Frontiers in Cardiovascular Medicine, 2023)
Background. Third generation drug eluting stents (DES) potentially offer better technical performance and reduced neointimal proliferation than previous generation DES. The XLIMIT non inferiority trial evaluated the performance of the Xlimus (a novel Sirolimus Eluting Coronary Stent System) in terms of endothelization and tissue healing compared to the bioresorbable polymer Synergy DES.Methods. A total of 177 patients undergoing PCI were randomized in a 2:1 ratio (2 Xlimus:1 Synergy). The primary endpoints, defined as the in-stent neointimal volume weighted by the sum of the lengths of implanted stent (ISNV), and the in-stent percent neointimal volume obstruction (%VO) were evaluated at 6-9 months by means of Optical Coherence Tomography (OCT). Additional OCT parameters as well as clinical end-points were also collected.Results. Most of the patients were males (77.4%), the mean age was 64 years. One third of the population had stable angina/silent ischemia.A total of 300 stents (237 lesions) were analysed: 198 (152 lesions) were in the Xlimus group, and 102 (85 lesions) in the Synergy one.The ISNV in the Xlimus group was 30.7±24.5 mm 3 while in the Synergy group was 26.5±26.7 mm 3 : the difference between the two means was 0.08(-0,04 -0,45), p=0.018, thus meeting the noninferiority hypothesis.The %VO was 16.3%±10.4% and 13.3%±10.8% between Xlimus and Synergy, respectively: the difference between the two means was 3.0 (-0,06 -4,2), (p=0.01), thus meeting the non-inferiority hypothesis.No difference was found with respect to secondary OCT endpoints as well as for clinical endpoints.The study results confirm that the biological interaction of the Xlimus and Synergy with the coronary artery is comparable, and that translates in very reassuring OCT parameters at follow up: as such, Xlimus is non inferior to Synergy (ClinicalTrials.gov Identifier: NCT03745053).